Research Microcultures as Socialization Contexts for Underrepresented Science Students - Thoman, Dustin B.; Muragishi, Gregg A.; Smith, Jessi L. (Psychological Science, 2017)
How much does scientific research potentially help people? We tested whether prosocial-affordance beliefs (PABs) about science spread among group members and contribute to individual students’ motivation for science. We tested this question within the context of research experience for undergraduates working in faculty-led laboratories, focusing on students who belong to underrepresented minority (URM) groups. Longitudinal survey data were collected from 522 research assistants in 41 labs at six institutions. We used multilevel modeling, and results supported a socialization effect for URM students: The aggregate PABs of their lab mates predicted the students’ own initial PABs, as well as their subsequent experiences of interest and their motivation to pursue a career in science, even after controlling for individual-level PABs. Results demonstrate that research labs serve as microcultures of information about the science norms and values that influence motivation. URM students are particularly sensitive to this information. Efforts to broaden participation should be informed by an understanding of the group processes that convey such prosocial values.